Molding and casting of the natural in wax for the foundry prototype - Martín Sánchez, Olegario; Palazón Cascales, Bartolomé (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This research on molding and casting aims to revalue the creative possibilities of the lost wax mold for the reproduction of living and inert bodies and fragments, both of people and animals. Analyzes the molding of life through the history of sculpture, emphasizing wax as a transitional sculptural material. The practice of this mold has certain advantages over the traditional lost mold and others of a permanent nature, such as the quality of reproduction of the model for lost wax casting, the economy of means and the reuse of the material.